Dampak BUMDES Terhadap Kesejahteraan Masyarakat di Desa Aik Batu Buding, Kabupaten Belitung, Provinsi Bangka Belitung. (UI Scholars Hub, 2019)
Village development is a priority in national development, because it is closely related to the third point of the President's Nawacita which states that it is developing Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state. This study aims to describe the impact of BUMDES on the welfare of rural communities. BUMDES is one of the programs to strengthen the role of the region. village aik batu buding, Belitung Districts, Bangka Belitung Islands Province has become one of the best BUMDES in the Province in 2016, because it is interesting to see the impact of the existence of BUMDES in the village on community welfare. This research was conducted using a qualitative approach and used in-depth interview and observation techniques. The results of the study have shown that BUMDES has had an impact on the village economy. BUMDES has an impact on community business development in Aik Batu Buding Village. In addition, BUMDES encourages people to start a new business according to the potential of the community. The impact of other BUMDES is to improve the level of children's education and improve public health